2020
DOI: 10.2147/prbm.s236735
|View full text |Cite
|
Sign up to set email alerts
|

<p>Wayfinding Strategy and Gender – Testing the Mediating Effects of Wayfinding Experience, Personality and Emotions</p>

Abstract: Background: Individual differences have been seen to play a key role in spatial orientation. Gender implications have been previously described but little is known about how other variables, such as wayfinding anxiety, emotional difficulties and wayfinding experience can mediate this relationship. Methods: A group of 269 participants were involved in this study and completed questionnaires on their self-reported allocentric orientation strategy, wayfinding experience and satisfaction with the ability for wayfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…2001) and higher spatial anxiety/uncertainty of women in the real environment (Lawton, C.A. et al 1996;Mendez-Lopez, M. et al 2020) do not translate into higher demand for smart navigation apps among women (Ženka, J. et al 2021). We, thus, do not confirm the assumption that people who are good at navigating themselves are not in an urgent need to use an indoor navigation system and may be less willing to adopt a smart indoor navigation system (Smirnov, M. 2007;Wichmann, J. and Leyer, M. 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2001) and higher spatial anxiety/uncertainty of women in the real environment (Lawton, C.A. et al 1996;Mendez-Lopez, M. et al 2020) do not translate into higher demand for smart navigation apps among women (Ženka, J. et al 2021). We, thus, do not confirm the assumption that people who are good at navigating themselves are not in an urgent need to use an indoor navigation system and may be less willing to adopt a smart indoor navigation system (Smirnov, M. 2007;Wichmann, J. and Leyer, M. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Women should be more sensitive to these issues for several reasons: a) they exhibit higher levels of uncertainty and spatial anxiety than men (Lawton, C.A. 1994;Mendez-Lopez, M. et al 2020); b) women perform slightly worse in spatial orientation in the real environment than men (Coluccia, E. and Louse, G. 2004); c) women rely on a 'route strategy' in their navigation (Lawton, C.A. 1994;Liao, H. and Dong, W. 2017), following the sequence of landmarks and left-right turns, while men prefer cardinal directions (North-South), global reference points (central square, airport, sun in the sky) and Euclidean distances (see also Lawton, C.A.…”
Section: Gender Age Education and Their Effects On Technology Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Human decision-making in wayfinding, influenced by environmental psychology, is easy in a well-arranged space, but it is not expected to be easy in an environment where various signs, shops, and crowds are intricately intertwined. Accordingly, studies are being conducted on achieving effective wayfinding in crowded spaces, such as commercial spaces and public spaces that cause confusion to users while wayfinding [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ] and in spaces that cause confusion for users, such as public transportation, etc. [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neurologically, age is correlated with a decreased volume of the frontal lobe and hippocampus. Mendez–Lopez, Fidalgo, Osma, and Juan [ 8 ] found that among the parameters that can influence wayfinding in a physical environment, gender difference significantly predicted effective wayfinding techniques. There was a difference between men and women in their self-reporting on space-oriented strategies [ 44 ] and the degree of confidence in their ability to solve spatial tasks.…”
Section: Introductionmentioning
confidence: 99%